"Theodora" Way Station: How The Psychological Concept of Life Script Mirrors Neurocognitive Memory of the Future. (2nd October 2019) - Shustov, Dmitri I.; Tuchina, Olga D.
Abstract: This article illustrates the relationship between the contemporary understanding of the human capacity for prospection—the representation of possible futures—and the notion of life scripts. Prospection is viewed as a vehicle for transgenerational trauma transmission and as a means of organizing and predicting future experience in line with "memories of the future" based on clients' historical experience. The authors argue that episcript content and its effects constitute the scene, and the process of scene construction relates to family-specific behaviors. The semantic scaffolding that guides the transmission is related to difficulties in psychosocial functioning. The template representation of the future in the long-term memory of people who are yet to receive the episcript may be represented by a neural network showing minimal activity, which can be compared to an empty station waiting for a train, the train in this instance symbolizing the episcript.